2021
DOI: 10.12998/wjcc.v9.i6.1293
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate vs propofol in coronary heart disease patients undergoing major noncardiac surgery: A randomized clinical trial

Abstract: BACKGROUND The ideal depth of general anesthesia should achieve the required levels of hypnosis, analgesia, and muscle relaxation while minimizing physiologic responses to awareness. The choice of anesthetic strategy in patients with coronary heart disease (CHD) undergoing major noncardiac surgery is becoming an increasingly important issue as the population ages. This is because general anesthesia is associated with a risk of perioperative cardiac complications and death, and this risk is much hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Dai et al found that propofol‐based anesthesia was associated with significantly higher incidences of bradycardia, hypotension, ST‐T segment abnormalities, and ventricular premature beats in patients with coronary heart disease undergoing noncardiac surgery under general anesthesia. 21 Kleiman RB et al confirmed that remimazolam did not prolong QT interval and did not increase the risk of ventricular arrhythmia. 22 In this study, the hemodynamics of the remimazolam induction group was more stable, the incidences of hypotension, and the cumulative norepinephrine doses used per patient, averaged per group were lower than those in the propofol induction group during anesthesia induction of patients undergoing valve replacement surgery under CPB, which was undoubtedly more favorable for patients undergoing valve replacement surgery.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Dai et al found that propofol‐based anesthesia was associated with significantly higher incidences of bradycardia, hypotension, ST‐T segment abnormalities, and ventricular premature beats in patients with coronary heart disease undergoing noncardiac surgery under general anesthesia. 21 Kleiman RB et al confirmed that remimazolam did not prolong QT interval and did not increase the risk of ventricular arrhythmia. 22 In this study, the hemodynamics of the remimazolam induction group was more stable, the incidences of hypotension, and the cumulative norepinephrine doses used per patient, averaged per group were lower than those in the propofol induction group during anesthesia induction of patients undergoing valve replacement surgery under CPB, which was undoubtedly more favorable for patients undergoing valve replacement surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Dai et al found that propofol‐based anesthesia was associated with significantly higher incidences of bradycardia, hypotension, ST‐T segment abnormalities, and ventricular premature beats in patients with coronary heart disease undergoing noncardiac surgery under general anesthesia 21 . Kleiman RB et al confirmed that remimazolam did not prolong QT interval and did not increase the risk of ventricular arrhythmia 22 .…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia is associated with cardiovascular depression and disruption of the autonomic nervous control system by anesthetic agents, which leads to redistribution of intravascular volume, thus resulting in PIHO. Etomidate is considered to be one of the most suitable anesthetic induction drugs because of its reliable sedation and hemodynamic stability ( Aggarwal et al, 2016 ; Mohr et al, 2020 ; Dai et al, 2021 ). The lack of hemodynamic depression is a good characteristic of remimazolam ( Doi et al, 2020a ; Doi et al, 2020b ; Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, propofol has a strong circulatory inhibitory effect, which often causes a significant drop in blood pressure, which is more pronounced in geriatric patients or patients with insufficient effective circulating blood volume. Because etomidate has little effect on circulation [ 7 , 8 ], it is often used for induction in geriatric patients, but etomidate does not inhibit the upper airway reflex, and it can make LMA insertion very difficult when used alone, so it needs to be combined with opioids. Among the opioids used, sufentanil is often used for anesthesia in the elderly.…”
Section: Introductionmentioning
confidence: 99%